Recovery and resilience strategies through strengthening post-pandemic coordination in Palembang City - Martina Martina; Alfitri Alfitri; Slamet Widodo (Universitas Merdeka Malang, 2025)
The lack of studies on post-pandemic in Indonesia, especially at the local level, has prompted this study to fill the gap. The purpose of this study is to analyze the recovery and resilience strategies implemented by the Palembang City government in facing post-pandemic challenges, with a focus on strengthening cross-sector coordination to increase the effectiveness of public policies. This research method uses a descriptive approach, with data collection through interviews, field notes, and official documents. NVivo 12 was chosen as the analysis tool to assist data mapping. The main findings of this study indicate that the Palembang City government has implemented various post-pandemic recovery and resilience strategies, including improving health services, economic support for SMEs, and implementing health protocols. In addition, strengthening cross-sector coordination is key to supporting the implementation of these policies. However, challenges such as the lack of data integration and coordination between sectors still need to be addressed to increase the effectiveness of public policies in the post-pandemic era. This could help the government to be better prepared for future crises.